Răspuns :
Răspuns:
[tex]\frac{2}{3}[/tex]
Explicație pas cu pas:
x = [tex]\sqrt{3} + 2 : \sqrt{3}[/tex]
x = [tex]\frac{\sqrt{3}}{1} + \frac{2}{\sqrt{3}}[/tex]
x = [tex]\frac{\sqrt{3}}{1} + [tex]\frac{2\sqrt{3}}{3}[/tex]
x = [tex]\frac{5\sqrt{3}}{3}[/tex]
x ÷ y - 1 =
[tex]\frac{5\sqrt{3}}{3}[/tex] × [tex]\frac{1}{\sqrt{3}}[/tex] - 1
[tex]\frac{5\sqrt{3}}{3}[/tex] × [tex]\frac{\sqrt{3}}{3}[/tex] - 1
[tex]\frac{15}{9} - \frac{1}{1}[/tex]
[tex]\frac{15}{9} - \frac{9}{9}[/tex]
[tex]\frac{6}{9}[/tex] = [tex]\frac{2}{3}[/tex]